2021
DOI: 10.3389/fcvm.2021.693912
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Prognostic Value of Lung Ultrasound B-Lines in Acute Heart Failure With Concomitant Pneumonia

Abstract: Purpose: To evaluate the potential confounding effect of concomitant pneumonia (PNM) on lung ultrasound (LUS) B-lines in acute heart failure (AHF).Methods: We enrolled 86 AHF patients with (31 pts, AHF/PNM) and without (55 pts, AHF) concomitant PNM. LUS B-lines were evaluated using a combined antero-lateral (AL) and posterior (POST) approach at admission (T0), after 24 h from T0 (T1), after 48 h from T0 (T2) and before discharge (T3). B-lines score was calculated at each time point on AL and POST chest, dividi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
(77 reference statements)
0
7
0
Order By: Relevance
“…As one of the important components of immunoglobulins, IgM has the same characteristics as CRP to exclude the influences of individual differences, shows a high sensitivity and is often used for clinical differential diagnosis [28,29]. Other clinical studies have shown that ABC count is also an important indicator commonly used to determine bacterial infection in patients, but it is susceptible to a number of factors that can lead to a lower percentage of positivity compared to indicators such as CRP and IgM [30,31]. However, this phenomenon was not reflected in the data from this study, which may be related to the small sample size of this study and the exclusion of differences in age, gender and other factors [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…As one of the important components of immunoglobulins, IgM has the same characteristics as CRP to exclude the influences of individual differences, shows a high sensitivity and is often used for clinical differential diagnosis [28,29]. Other clinical studies have shown that ABC count is also an important indicator commonly used to determine bacterial infection in patients, but it is susceptible to a number of factors that can lead to a lower percentage of positivity compared to indicators such as CRP and IgM [30,31]. However, this phenomenon was not reflected in the data from this study, which may be related to the small sample size of this study and the exclusion of differences in age, gender and other factors [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Russel et al [31] reported a coefficient of 0,74 after a trial of approximately 11 exams and two hours of theoretical class. Miglioranza et al [25] reported a coefficient of 0.98 (95% IC : 0.98-0.99 ; p < 0.0001) in a set of 20 consecutive patients, M. Mazzola et al [32] found a coefficient of 0.98 (p < 0.0001) in 50 LUS videos evaluated by an expert reader.…”
Section: Strenghsmentioning
confidence: 97%
“…Then, the univariate and multivariate logistic regression, least absolute shrinkage selector operator (LASSO) regression analysis, nomogram, receiver operating characteristic (ROC) curve plot, and internal validation were performed to construct the visualization model and validation. Thus, we aimed to develop a preliminary clinical prediction model for the prognosis of pneumonia complicated with HF based on NGS of metagenome and hope that this model will be helpful to the assessment of prognosis of HF with pneumonia [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Investigation on the clinical trials of PARADIGM-HF [4] and PARAGON-HF [5] demonstrated that pneumonia incidence was high in patients with HF followed by 4-fold higher mortality [6]. However, the predictive factors of prognosis in patients with pneumonia complicated with HF were not fully investigated yet [7][8][9][10], especially with the help of next-generation sequencing (NGS) of metagenome.…”
Section: Introductionmentioning
confidence: 99%